Penentuan Mahasiswa Berprestasi dengan Menerapkan Metode Multi Attribute Utility Theory (MAUT) - Wulan Kartika Murti; Agung Triayudi; Mesran Mesran (STMIK Budi Darma, 2023)
Being an outstanding student in higher education is certainly a positive and proud thing. Where national education aims to develop the potential of students, in order to become educated, creative students and become democratic and responsible citizens. In determining outstanding students, there are several criteria that must be met by each student as a condition for determining outstanding students. The problem that occurs is that sometimes there are obstacles when assessing the criteria set for each prospective participant. To help the evaluation team in determining outstanding students, a decision support system is needed, sometimes experiencing obstacles when assessing the criteria set for each candidate. In the assessment carried out directly there are prospective candidates who do not meet the criteria standards but excel in other criteria. The Multi Attribute Utility Theory (MAUT) method is a quantitative comparison method used to convert several interests into numerical values on a scale of 0-1 with 0 representing the worst value and 1 the best value. The result of this research is a student determination decision that has the highest score value, namely Netralman (A1) with a utility value of 0.462.